Ecological Service Function Evaluation of Urban Greening Shrubs in Guanzhong Region, Shaanxi Province - Han Wenyue; Gai Shuaizi; Liu Zengwen; Xu Rui; Wang Songwei; Zhang Yu (Shuitu baochi tongbao)
[Objective] The landscapes and ecological service functions were comprehensively evaluated in order to provide scientific guidance for the selection of urban greening shrub species. [Methods] Several indexes including landscape service functions (such as greenness quantity, leaf greening period, aesthetic degree) and ecological service functions (such as water conservation, dust retention, oxygen generation while carbon fixation, cooling while humidifying, noise reduction) were investigated and measured, and a comprehensive evaluation model was built by using principal component analysis (PCA) to evaluate 26 common urban greening shrub species in the Guanzhong region of Shaanxi Province. [Results] ① According to the ranking results of the comprehensive evaluation of landscape service functions, Ligustrum quihoui, Viburnum odoratissinum, Photinia fraseri, Chaenomeles speciosa, Buxus megistophylla, Pittosporum tobira, and Buxus bodinieri received the highest grades of comprehensive evaluation (0.63—1.96) and proved to be the preferred shrub species in landscape beautification. ② According to the ranking results of the comprehensive evaluation of ecological service functions, L. quihoui, V. odoratissinum, C. speciosa, P. fraseri, P. tobira and Pyracantha fortuneana received the highest grades of evaluation (0.70—3.04) and performed outstanding in ecological improvement. ③ According to the comprehensive evaluation of landscape services combined with ecological services, the shrubs that received higher grades were L. quihoui (3.54), V. odoratissinum (2.86), C. speciosa (2.05), P. fraseri (1.72), and P. tobira (1.38). [Conclusion] Shrub species with higher grades should be selected preferentially according to different needs, thous can provide a basis for the selection and cultivation of greening shrub species in urban ecological gardens.